Intra and intersentential code-switching phenomena in modern Malay songs - Wan Nur Syaza Sahira Wan Rusli; Azianura Hani Shaari; Siti Zaidah Zainuddin; Ng, Lay Shi; Aizan Sofia Amin (Penerbit Universiti Kebangsaan Malaysia, 2018)
Code-switching has been used in many languages by many different groups of people or speech communities, but little is known about how and why they are used as communicative strategies in modern song lyrics. This paper aims to explore and describe the recent phenomenon of English code-switching in modern Malay songs. 25 modern Malay songs were selected and analysed using Content Analysis. The analysis was made based on Poplack’ Theory as well as the functions of code-switching proposed by Appel and Musyken. Two types of codeswitching commonly used in modern Malay songs were discovered. They were intrasentential and intersentential code-switching. The classification of the functions of code-switching was then made based on the six functions of code-switching, which are referential, directive, expressive, phatic, metalinguistic, and poetic. The findings of this research also indicate other functions of code-switching that demonstrate bilingual creativity among songwriters in Malaysia. In conclusion, the findings of this study indicated that code switching in Modern Malay songs is not just a random switch from one code to another but carries certain social functions that emphasize on the establishment of people’s intimacy, solidarity and local identity.